Effect of pressure cycling on Iron: Signatures of an electronic instability and unconventional superconductivity - Pedrazzini, Pablo (2013)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina